3x - 6y + 2z - 5x - 3y + 8z

3x - 6y + 2z - 5x - 3y + 8z = (3x - 5x) + (-6y - 3y) + (2z + 8z) = -2x - 9y + 10z

Question

Asked 3/7/2013 4:03:16 PM

Updated 6/26/2014 12:29:12 AM

1 Answer/Comment

Edited by jeifunk [6/26/2014 12:44:43 AM]

Rating

3

3x - 6y + 2z - 5x - 3y + 8z

= (3x - 5x) + (-6y - 3y) + (2z + 8z)

= -2x - 9y + 10z

= (3x - 5x) + (-6y - 3y) + (2z + 8z)

= -2x - 9y + 10z

Added 6/26/2014 12:29:12 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 12:44:36 AM]

27,102,374

questions answered

There are no comments.